Reimagining Economic Wellbeing and Justice: The Wasaṭiyya Framework in Islamic Economics - Azzuhri, Anggi; Fadhil, Haidar Masyhur (Economica: Jurnal Ekonomi Islam, 2022)
This article explores the foundations and instruments of Islamic economics, with a focus on the wasaṭiyya (moderation) mindset. The concept of Iqtiṣād, which signifies balance and fairness, lies at the core of Islamic economic principles, as reflected in the Qur’ān and developed by scholars such as Al-Ghazālī, Ibn Khaldūn, and Bāqir Al-Ṣadr. Bāqir Al-Ṣadr positions Islamic economics as a middle path between capitalism and socialism, advocating an ethical system that promotes justice and sustainable growth. The study examines key financial instruments—zakāt, waqf, kharāj, jizya, and sukūk—which are designed to reduce poverty, promote wealth circulation, and ensure fair resource distribution. It also addresses challenges such as economic crises, regulatory failures, and societal greed, which threaten the sustainability of wellbeing. Through an analysis of primary Islamic texts and the works of major scholars, this article compares Islamic economic thought with capitalist and socialist models, highlighting its unique approach to wellbeing and justice. Modern scholarly contributions further enhance the discussion, providing insights into the practical applications of these principles today. Ultimately, the wasaṭiyya framework is shown to offer a balanced and resilient framework for addressing contemporary economic challenges, positioning Islamic economics as a viable alternative to conventional systems in the pursuit of human wellbeing and economic justice.